IMPLEMENTATION OF THE ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) SYSTEM THROUGH TRAFFIC CCTV SURVEILLANCE AS AN EFFORT TO CRACK DOWN ON VIOLATORS - Widya Maylin Sinurat; Rizkan Zulyadi; Serimin Pinem (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study analyzes the implementation of the Electronic Traffic Law Enforcement (ETLE) system through traffic CCTV surveillance as an effort to enforce traffic violations in Medan City. The objectives of this research are to examine the legal basis of the ETLE system, analyze its implementation by the Traffic Directorate of the North Sumatra Regional Police, and identify obstacles encountered in its application. This research employs a normative juridical method with a descriptive-analytical approach, utilizing primary legal materials in the form of statutory regulations and secondary legal materials from legal literature and scholarly works. The results indicate that the legal foundation of the ETLE system is established under Law Number 22 of 2009, Government Regulation Number 80 of 2012, and Police Regulation Number 8 of 2023, which collectively provide legal certainty for electronic-based traffic law enforcement. The implementation of ETLE in Medan City has been conducted through public socialization and CCTV-based monitoring to enhance efficiency and objectivity in traffic law enforcement. However, several obstacles remain, including technical limitations of CCTV facilities, weather conditions, low public awareness, inaccurate vehicle data, and the use of fake license plates. These challenges affect the effectiveness of ETLE implementation and require improved infrastructure and inter-agency coordination.